Manfaat Teknologi Informasi dan Komunikasidalam Pembelajaran Kewarganegaraan di Kelas 5 SDN 2 Jerowaru - Samsul Hadi; Ahmad Jalaluddin; Amrullah; Khairul Fahmi; Muhamad Zaini (Pendidikan Al-Gafari, 2024)
Globalization has resulted in the easy penetration of very sophisticated technology from developed countries to developing countries such as Indonesia (global village). In this era, the role of technology is vital, if people in a country are unable to optimize the role of technology, it can be said that information and communication technology will be left behind by other countries. This study aims to explore and describe the benefits of information and communication technology (ICT) in civics learning in grade 5 of Elementary School. This study uses a qualitative research method with a descriptive approach, involving classroom observations, in-depth interviews with teachers and students, and analysis of learning documentation using ICT. The results of the study indicate that the integration of ICT in civics learning in grade 5 of Elementary School provides various significant benefits. First, ICT increases student involvement in the teaching and learning process. Tools such as multimedia presentations, educational videos, and interactive applications make students more interested and enthusiastic about learning. Second, the use of ICT helps students understand civic concepts better through visualizations and simulations that facilitate understanding of abstract material. Third, teachers feel helped by the existence of information and communication technology in delivering lesson materials more effectively and efficiently, as well as facilitating the evaluation process through online quizzes and tests that can be assessed directly.